Atmospheric aerosol-microplastics intake and deposition in the alveolar region by considering dynamic behavior of acinar airways - Hamidreza Mortazavy Beni; Hamed Mortazavi; Puchanee Larpruenrudee; YuanTong Gu; Emilie Sauret; Mohammad S. Islam (PLoS ONE, 2025)
Background and objective Atmospheric aerosols from different industrial and natural sources enter the airways during inhalation. The smaller respirable aerosols enter the alveolar sacs and, depending on the residence time and toxicity, create severe respiratory health hazards. The physiological movement of the alveolar sacs is an important feature of breathing dynamics. Therefore, the knowledge of the dynamic behavior of the alveolar airways during airflow and aerosol transport is essential for the accurate health risk assessment of respiratory aerosols. Methods This study analyzed the physiological movements of the alveolar sac and its impact on airflow and particle deposition in the acinar region. In the present study, the dynamic acinar model uses a Computational Fluid-Particle Dynamics (CFPD). The boundary condition of moving walls is presented by introducing a novel strategic motion function of the alveoli (Eq. 5) compatible with the physiological function of the lung. Results The results of the present study indicated that particle density is a determining factor in increasing the percentage of particle pollution deposition lower than 3 µm. The study also reports that the air amplitude velocity (~0.01 vs. 0.00085 m/s) is a crucial index in the particle pollution deposition in alveoli. Conclusions To date, several studies analyzed the airflow in acinar sections. However, a comprehensive analysis of the physiological behavior of the alveolar sacs is missing in the literature. The specific findings of this study would improve the knowledge of airborne particle transmission in the alveolar zone.